Solar Radiation Potential at Four Sites of Nepal - Pondyal, Khem N; Bhattarai, Binod K; Sapkota, Balkrishna; Kjeldstad, Berit (Journal of the Institute of Engineering, 2012)
The intensity of solar radiation available at the horizontal surface are measured by a CMP6 Pyranometer in Biratnagar (26.45°N, 87.27°E), Pokhara (28.22°N, 83.32°E), Kathmandu (27.72°N, 85.32°E ) and Lukla (26.69°N,86.73°E), which are 72m, 800m, 1350m, and 2850m, above from the sea level. This paper compares the seasonal and altitude variations of total solar radiation measured at above mentioned sites. The maximum total solar radiation of about 704.51 W/m2, 815.97 W/m2 777.27 W/m2 and 914.03 W/m2, are observed in Biratnagar, Pokhara, Kathmandu, and Lukla respectively. Solar radiation available in any location is affected by topography and pollution. It is found that the more solar energy is available during spring than in summer in Lukla. The solar radiation is observed higher in Pokhara than in Kathmandu. It might be due to absorption of solar energy by air pollutants which are higher in Kathmandu as compared to Pokhara.In addition we also discussed the diurnal variation of measured and calculated data of solar radiation on clear sky day. The annual average solar energy measuring 4.95, 5.44, 5.19 and 4.61 kWh/m2/day is found in Biratnagar, Pokhara Kathmandu and Lukla respectively. DOI: http://dx.doi.org/10.3126/jie.v8i3.5944 JIE 2011; 8(3): 189-197